Análise do conforto de pacientes submetidos a transplante de rim: contribuições para o cuidado de enfermagem - Calazans, Cecília Carla Barroso (2024)
Kidney transplantation (KTx) consists of the transfer of a healthy kidney from a donor (living or deceased) to a person with chronic kidney disease (CKD). In this context of comprehensive care for the transplant recipient, the role of the nurse stands out, as this professional actively participates in the process together with the patient. Given this perspective, holistic care must be based on nursing theories, which provide knowledge for safe decision-making, ensuring the safety of the kidney transplant recipient. Therefore, among contemporary theories, in the field of nursing, the contributions of Katharine Kolcaba stand out, with the development of the Comfort Theory. With this, the objective was to analyze the level of comfort of people with chronic kidney disease undergoing kidney transplantation three months to one year after surgery. In the method, the chosen methodological structure was a mixed study, with a descriptive-cross-sectional design. The study was conducted with 46 transplant patients who undergo outpatient follow-up at a large public university hospital located in the city of Fortaleza, Ceará. As a quantitative result, it was found that the domain with the highest level of comfort was the psychospiritual domain (57.95) and the one with the lowest level of comfort was the sociocultural domain (31.89). The qualitative results were categorized into four thematic units: Physical, Environmental, Sociocultural and Psychospiritual. In the Physical Context, pain was written most frequently by the participants after the transplant, often being associated with the various invasive procedures. In the Environmental Context, the components of the environment such as light, smell, sound, temperature and uncomfortable furniture stood out. In the Sociocultural Context, it was found that family support allowed great representation in improving comfort, as it helps the transplant patient to deal with the changes and restrictions arising from this new stage of life. In the Psychospiritual Context, it was proven that negative thoughts were overcome, despite some adverse situations that the transplant recipient goes through during the process. It is also worth highlighting the importance of spirituality and religiosity, since the patient sought strength in some spiritual being to maintain physical and mental balance. Thus, it was found, as proposed by Katharine Kolcaba's Theory, that comfort represents a basic human need. In view of this, it is necessary to achieve it so that the individual can achieve self-realization and autonomy in the kidney transplant process.